2020
DOI: 10.1016/j.dcn.2020.100852
|View full text |Cite
|
Sign up to set email alerts
|

The association between parenting and the error-related negativity across childhood and adolescence

Abstract: Anxiety is the most common form of psychopathology, and it is often characterized by chronic impairment across the lifespan. Researchers have identified core neural markers that confer risk for anxious outcomes. An increased error-related negativity (ERN) in anxious individuals has been shown to prospectively predict onset of anxiety disorders across development. Hence, it is critical to examine environmental factors that may shape the ERN. In the current study, we use a large sample of 170 female adolescents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 118 publications
(151 reference statements)
3
12
1
Order By: Relevance
“…Finally, we attempted to integrate the current findings with prior work concerning the role of parenting experiences and child anxiety. An investigation of parenting and anxiety by Chong et al (2020) found that child age moderated the relation between parenting style and the ERN, such that harsher parenting was associated with a more negative ERN only for younger children. Chong et al (2020) also found that the association between parenting style and anxiety disorder diagnosis was mediated by the ERN, but only for younger children.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we attempted to integrate the current findings with prior work concerning the role of parenting experiences and child anxiety. An investigation of parenting and anxiety by Chong et al (2020) found that child age moderated the relation between parenting style and the ERN, such that harsher parenting was associated with a more negative ERN only for younger children. Chong et al (2020) also found that the association between parenting style and anxiety disorder diagnosis was mediated by the ERN, but only for younger children.…”
Section: Resultsmentioning
confidence: 99%
“…The present sample was drawn from a larger, NIMH-funded, longitudinal study (R01 MH097767) investigating neural risk markers for depression in females from a community sample. It is important to note that previous studies have been published using this dataset ( Chong et al, 2020 , Gorday and Meyer, 2018 , Meyer et al, 2018 , Meyer et al, 2021 ); however, none of the previous studies focused on the relationship between the ERN and stressful life events. Previous studies using this larger dataset have investigated the relationship between anxiety and the ERN ( Meyer et al, 2018 , Meyer et al, 2021 ), parenting styles and the ERN ( Chong et al, 2020 ), and puberty and the ERN ( Gorday and Meyer, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the decision on the length of each time window would be critical, especially for waveforms with multiple adjacent ERP components. Other studies utilized principal component analysis (Bonmassar et al, 2020) and automated peak detection (Chong et al, 2020). by pediatric and adult ERP researchers (Brooker et al, 2019;Keil et al, 2014;Luck & Gaspelin, 2017), it is important that whatever method for ERP component latency selection is applied, researchers practice persistence in reporting and justifying their selection of ERP time windows.…”
Section: Discussionmentioning
confidence: 99%
“…Often heard cases of deviations in children's behavior whether in childhood, adolescence or adulthood where is actually reflects the success or failure of the process of caring for his family [8]. Errors in parenting can also have an impact when they grow up [9]. Children will feel traumatized if parenting in his family is carried out in a coercive manner [10].…”
Section: Introductionmentioning
confidence: 99%